Transverse fracture of a tooth root as a consequence of long-term traumatic occlusion-A case report - Małgorzata Skucha-Nowak; Marta Cieślik-Wegemund; Dariusz Skaba; Marta Tanasiewicz; Ewa Pawliszyn (Elsevier, 2010)
The purpose of this paper is to present treatment results of transverse root fracture in an adult patient caused by long-term traumatic occlusion resulting from use of a wrongly fitted upper-frame denture. A 44-year-old male patient had a transverse displaced fracture at one-third of the crown-root boundary area of tooth 42. The tooth was treated endodontically after prior positioning of fragments in 1 plane. The canal was filled, and a "Splint It" splint was applied for the period of 1 year. The patient returned for check-ups after 2 and 2.5 years, at which time X-rays were taken. Our goal was achieved through preservation of the patient's own completely recovered and fully functional tooth.